Zarządzanie majątkiem obrotowym w procesie kreowania wartości przedsiębiorstwa - wyniki badań - Szymański, Piotr (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article contains the results of a survey of current assets management and value based management in 191 enterprises from south-western Poland. This research consists of 82 questioners and 1.734 financial statements from 1991 until 2003. The study proves that too many Polish enterprises destroy their value. Despite the fact that average 73% companies have net profit, only 50% of them create value. One of the main reasons is the weakness of current asset management. In this study, the companies were divided in to three groups. First group involved enterprises which created value for shareholders, second group included enterprises which destroyed value for shareholders and third group involved enterprises about which it was difficult to say if they created or destroyed value for shareholders. The comparison shows that enterprises from first group better manage current assets than other groups. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 538-567